FORMULATION AND IN-VITRO EVALUATION OF TRANSDERMAL MATRIX PATCHES OF DOXOPHYLLINE. - Kaur, Khushpal; Kaur, Preetinder; Jalhan, Sunny; K Jain, Upendra (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The objective of the present study was to fabricate matrix type transdermal patch with varied proportion of hydrophilic (HPMC E-50) and (PVP) combination incorporating the drug Doxophylline and to execute the physicochemical and in vitro assessment. The motive was to provide the delivery of Doxophylline at a controlled rate across the intact skin to attain a therapeutically effective drug level for a longer time span from transdermal matrix patch. Method: Prefomulation studies and evaluation was done by using different parameter such as Partition coefficient, Physicochemical Compatibility of Drug and Polymer, Physical appearance, Thickness Measurement, Folding Endurance, Weight variation, Percentage moisture lost, Percentage moisture uptake, Drug content Determination. Result: The results shows that patches of Doxophylline obtained by the solvent evaporation method had acceptable physicochemical characteristics and satisfactory percentage drug release. Conclusion: The main conclusion of my work was formulating the Doxophylline transdermal system was to prolong the drug release time, reduce the frequency of administration and to improve patient compliance. Six formulations were prepared using two polymers in different ratios along with plasticizers and penetration enhancer. Keywords: Matrix transdermal patch, Doxofylline, Hydroxy propyl methyl cellulose E-50, Poly vinyl pyrrolidone, Dimethyl sulfoxide, Polyethyleneglycol 400.